Sedentarization of nomadic people and citizens’ perceptions in Djibouti - Bouh Omar Ali; Yutaka Ito; Shuichi Oyama; Sergio Azael May-Cuevas; Sawahiko Shimada; Yuki Yamamoto (Development Studies Research)
Nomadic communities often face limited access to basic infrastructure and public services. Integrating these communities into sustainable development strategies should be a priority, aligning with the United Nations’ principle of ‘Leave no one behind,’ and is particularly critical for countries with arid regions. However, the public perceptions of policies addressing nomadic communities remain understudied, leading to delays in effective policy implementation. We conducted a survey among college students to examine citizens’ perceptions of policies affecting nomadic communities in Djibouti. Using Best – Worst Scaling, we evaluated policy priorities among seven socioeconomic options, including the sedentarization policy for nomadic people. Although the sample population was relatively well-educated and biased toward higher education levels compared with the national average, this study is the first attempt to explore citizens’ perspectives on policies involving nomadic communities in a developing country. Sedentarization ranked as the lowest priority out of the seven policy options, while employment and health-related policies were prioritized. These results suggest that citizens prioritize immediate livelihood concerns over policies focusing on nomadic people. The findings highlight the need for international support and interventions to enhance citizens’ understanding of the significance of policies for nomadic communities and to facilitate their effective implementation.